Imidazole antifungal drugs inhibit the cell proliferation and invasion of human breast cancer cells - Bae, Sung Hun; Park, Ju Ho; Choi, Hyeon Gyeom; Kim, Hyesook; Kim, So Hee (Biomolecules and Therapeutics, 2018)
Breast cancer is currently the most prevalent cancer in women, and its incidence increases every year. Azole antifungal drugs were recently found to have antitumor efficacy in several cancer types. They contain an imidazole (clotrimazole and ketoconazole) or a triazole (fluconazole and itraconazole) ring. Using human breast adenocarcinoma cells (MCF-7 and MDA-MB-231), we evaluated the effects of azole drugs on cell proliferation, apoptosis, cell cycle, migration, and invasion, and investigated the underlying mechanisms. Clotrimazole and ketoconazole inhibited the proliferation of both cell lines while fluconazole and itraconazole did not. In addition, clotrimazole and ketoconazole inhibited the motility of MDA-MB-231 cells and induced G1-phase arrest in MCF-7 and MDA-MB-231 cells, as determined by cell cycle analysis and immunoblot data. Moreover, Transwell invasion and gelatin zymography assays revealed that clotrimazole and ketoconazole suppressed invasiveness through the inhibition of matrix metalloproteinase 9 in MDA-MB-231 cells, although no significant changes in invasiveness were observed in MCF-7 cells. There were no significant changes in any of the observed parameters with fluconazole or itraconazole treatment in either breast cancer cell line. Taken together, imidazole antifungal drugs showed strong antitumor activity in breast cancer cells through induction of apoptosis and G1 arrest in both MCF-7 and MDA-MB-231 cells and suppression of invasiveness via matrix metalloproteinase 9 inhibition in MDA-MB-231 cells. Imidazole drugs have well-established pharmacokinetic profiles and known toxicity, which can make these generic drugs strong candidates for repositioning as antitumor therapies.
Keywords: Apoptosis; Breast cancer; Cell proliferation; Imidazole; Invasion; MMP9